Penerapan Strategi Pembelajaran Berorientasi Aktivitas Siswa Dalam Meningkatkan Hasil Belajar Siswa (Studi Di SD IT Al Uswah Tuban) - Ahmad Suyanto (LPPM Institut Agama Islam Al-Hikmah Tuban, 2019)
Abstract, Thematic learning is learning that uses themes. One theme for several subjects. In this 2013 curriculum integrated thematic learning is designed. It means theme-based learning with several subjects in it. Student books and teacher books are currently one social studies subject with PPKn at the Primary School level. Learning that applies the 2013 curriculum teachers are required to be more active and creative. Teachers who only apply one strategy and one method are not enough. Especially thematic which intersects with PPKn, IPS, and Indonesian Language material, sometimes still traditional, such as lectures, memorization, and assignments, summarizes and only works on problems. With this, children are not invited to interact in two directions, let alone find their own concepts (inquiry). This kind of learning will affect the motivation and student learning outcomes. From the data on the initial learning outcomes of VIA grade students at SDIT Al-Uswah Tuban, the students' completeness score was only 61% and the class average was 74.65 even though the class was declared to have been completed if it received 85%. The existence of such problems, the authors find a drug or formulation in the form of a strategy, this strategy is SPBAS or learning strategies that are activity oriented students using group discussion methods. Research on the application of SPBAS with group discussion methods in improving student learning outcomes at Theme 8 (My Earth) class 6A SDIT Al Uswah Tuban is focused on two issues. First